Conceptualizing the Organization of Surgical Services; Comment on "Decentralization and Regionalization of Surgical Care: A Review of Evidence for the Optimal Distribution of Surgical Services in Low- and Middle-Income Countries" - Sara A. Kreindler (Kerman University of Medical Sciences, 2021)
According to Iverson and colleagues' thoughtful analysis, decisions to decentralize or regionalize surgical services must take into account contextual realities that may impede the safe execution of certain delivery models in lowand middle-income countries (LMICs), and should be governed by procedure-related considerations (specifically, volume, patient acuity, and procedure complexity). This commentary suggests that, by shifting attention to the mechanisms whereby (de)centralization may exert beneficial impacts, it is possible to generate guidance applicable to countries across the socioeconomic spectrum. Four key mechanisms can be identified: decentralization (1) minimizes the need for patients to travel for care and, (2) obviates certain system-induced delays once patients present; centralization (3) facilitates the maintenance of a workforce with sufficient expertise to offer services safely, and (4) conserves resources by limiting the number of sites. The commentary elucidates how context- and procedure-related factors determine the importance of each mechanism, allowing planners to prioritize among them. Although some context factors have special relevance to LMICs, most can also appear in high-income countries (HICs), and the procedure-related factors are universal. Thus, evidence from countries at all income levels might be fruitfully combined into an integrated body of context-sensitive guidance.